A fast-heat battery system using the heat released from detonated supercooled phase change materials. (15th March 2021) - Ling, Ziye; Luo, Mingyun; Song, Jiaqi; Zhang, Wenbo; Zhang, Zhengguo; Fang, Xiaoming
Abstract: A heating strategy has been developed for the battery operated at low temperature, which can intelligently control the thermal storage and release of an inorganic phase change material (PCM): CaCl2·6H2O - carboxymethyl cellulose (CMC). With the 0.5 wt % CMC content, this PCM (melts at 25–30 °C) becomes stable in the subcooled state, making it possible to be used as the subcooled liquid at 5 °C to store the heat generated by the battery. The thermal energy stored in the subcooled PCM can be detonated to release by triggering the PCM to crystalize with a special device. The instant crystallization of this subcooled PCM heats the battery rapidly-which is at a rate up to 7.5 °C/min, higher than the battery without PCM (0.8 °C/min) or the battery with the no subcooled PCM(0.4 °C/min). The discharge capacity and power can be improved by 9.87% and 7.56%. This work presents a new method of heating by switching the subcooling of PCM on/off, which extends the application of PCMs to battery heating under low temperatures. This energy-free but efficient method could provide a better alternative to most active heating systems. Graphical abstract: Image 1 Highlights: A passive but rapid battery heating strategy with thermal release of subcooled PCM. The stable subcooling of PCM was used to preserve the latent heat. An effective trigger device for solidification of subcooled PCM is designed. The heating rate of this method is up to 7.5 °C/min. The discharge capacity and power of the battery were improved by 9.87% and 7.56%.